Risk of publication in worthless journals - Shrestha, Jiban; Subedi, Subash; Timsina, Krishna P.; Tripathi, Mahendra P. (Journal of Agriculture and Natural Resources, 2018)
Implementing research and publishing results is a crucial for a professional development, scientific communication and collaboration of any academicians, scholars, and researchers in science around the world. The timely dissemination of knowledge and scientific information in the global scientific community helps the development of science and worldwide recognition. The researchers working on scientific community cannot appreciate the value of evidence generated without publishing their work in right and quality journals. Therefore, authors should be careful about predatory or fake journals/publishers for communicating their scientific works. The objective of this study is to raise awareness on predatory or fake publishers/journals and of their dishonest publishing practices. In general, the predatory journal publishes without peer review and true editorial board, often publish mediocre or even worthless papers on charging high publication cost, citing fake and non-existing impact factors and mostly focused on private business motives. On the other hand, publishing in a high impact quality journals undoubtedly enhances the future career prospects, communication ability of authors and deliver concise research messages in the scientific field. Researcher of various disciplines and academic experience should aware with the lists of predatory journals/publishers which are available on Beall’s list in internet before publishing any research articles. Therefore, publishing in predatory/fake journals not only spoil or degrade academic reputations but also waste the time, resources and research message too.